Tanaman Gletang Pengusir Nyamuk Ramah Lingkungan Tanpa Bahan Kimia: Potensi Tridax procumbens sebagai Bioinsektisida Alami terhadap Aedes aegypti - JANNAH, ELOK WARDATUL (Maliki Interdisciplinary Journal, 2026)
Dengue Hemorrhagic Fever (DHF) remains a serious public health problem, especially in tropical countries like Indonesia. The intensive use of synthetic insecticides to control Aedes aegypti has led to various negative impacts, such as insect resistance, environmental pollution, and human health risks. This has prompted the need for safer and more sustainable vector control alternatives. This article presents a literature review of the potential of Tridax procumbens as a natural bioinsecticide based on the results of several studies. The study was conducted by examining the literature related to phytochemicals, larvicidal activity, repellent activity, and the biochemical mechanisms of the plant in affecting the physiological system of Aedes aegypti. The results of the study indicate that Tridax procumbens contains important secondary metabolites such as β-ionone, dodecanal, terpenoids, flavonoids, and aldehydes that have been proven to have insecticidal properties. These compounds work through the mechanisms of larval intestinal damage, energy metabolism disruption, respiratory disorders, and inhibition of the acetylcholinesterase enzyme in the mosquito nervous system. Based on the literature analysis, Tridax procumbens has great potential as a modern bioinsecticide that is effective, environmentally friendly, and has the potential to reduce the risk of synthetic insecticide resistance. Therefore, this plant deserves further development in various larvicidal and repellent formulations as part of an integrated vector control strategy.